Tongass Timber Reform Act : hearing before the Committee on Resources and the Subcommittee on Resource Conservation, Research, and Forestry of the Committee on Agriculture, House of Representatives, One Hundred Fourth Congress, second session, on H.R. 3659, a bill to amend the Tongass Timber Reform Act to ensure the proper stewardship of publicly owned assets . July 11, 1996--Washington, DC. - United States. Congress. House. Committee on Resources.; United States. Congress. House. Committee on Agriculture. Subcommittee on Resource Conservation, Research, and Forestry. (Washington : U.S. G.P.O. : For sale by the U.S. G.P.O., Supt. of Docs., Congressional Sales Office, 1996)
Mode of access: Internet.